Case Report: Maintenance Nivolumab in Complete Responder After Multimodality Therapy in Metastatic Pancreatic Adenocarcinoma - Yang, Shih-Hung; Lee, Jen-Chieh; Chen, Bang-Bin; Kuo, Sung-Hsin; Hsu, Chiun; Bai, Li-Yuan (Frontiers in Immunology, 2022)
Maintenance therapy is rarely considered in pancreatic ductal adenocarcinoma (PDAC). We describe the case of a 57-year-old man with metastatic PDAC treated with an initially full but subsequently de-escalated dose of combination chemotherapy due to intolerance to neurotoxicity. After a complete response to combined radiofrequency ablation for the liver metastasis and radiotherapy for the pancreatic tumor was achieved, chemotherapy was terminated and maintenance therapy was applied: nivolumab plus cytokine-induced killer cell therapy initially and then a de-escalated dosing interval of nivolumab monotherapy subsequently. No adverse events occurred during nivolumab therapy for more than 2 years, and the patient remains disease-free. To date, this is the first report of maintenance nivolumab after successful multimodality therapy in metastatic PDAC.